Angioinvasive Aspergillus-associated Stroke in an Immunocompetent Host Following Cardiac Surgery and ECMO. Issue 3 (May 2017) - Kavi, Tapan; Madan, Nikhil; Majic, Tamara; Rosengart, Axel; Maya, Marcel; Bannykh, Serguei; Lahiri, Shouri
Abstract : Introduction: Invasive cerebral aspergillosis is an uncommon cause of stroke among immunocompetent patients and has not been reported in association with cardiac surgery or extracorporeal membrane oxygenation (ECMO). We report the case of an immunocompetent host who developed aspergillus-associated stroke following coronary artery bypass graft (CABG) and ECMO. Case Report: A 59-year-old woman developed cardiogenic shock after 3-vessel-CABG requiring intra-aortic balloon pump placement and subsequent veno-arterial ECMO. Noncontrast computed tomography of the brain was suggestive of multiple bihemispheric ischemic infarcts. Postmortem pathologic analysis revealed aspergillus-associated inflammation of blood vessels and ischemic and petechial hemorrhagic strokes in the affected territories. Discussion and Conclusions: Ischemic infarcts in the setting of CABG or ECMO are often presumed to be thromboembolic from the heart or device, related to underlying hemodynamic instability, or due to a clinically apparent systemic infection such as endocarditis. This report suggests that invasive cerebral aspergillosis should be considered in seemingly immunocompetent patients following CABG or ECMO. The mechanism is unclear, but may be related to systemic inflammatory dysregulation resulting in increased susceptibility to uncommon pathogens.